Design of a fork-tuned antenna for Ultra-WideBand (UWB) communications - Mohd. Ezanuddin, Abdul Aziz; Soh, Ping Jack; Mohd Suhaizal, Abu Hassan; Norazliana, M. N. (Institute of Electrical and Electronics Engineering (IEEE), 2010)
Link to publisher's homepage at http://ieeexplore.ieee.org/